2009
DOI: 10.1101/gr.089714.108
|View full text |Cite
|
Sign up to set email alerts
|

Single-pass classification of all noncoding sequences in a bacterial genome using phylogenetic profiles

Abstract: Identification and characterization of functional elements in the noncoding regions of genomes is an elusive and timeconsuming activity whose output does not keep up with the pace of genome sequencing. Hundreds of bacterial genomes lay unexploited in terms of noncoding sequence analysis, although they may conceal a wide diversity of novel RNA genes, riboswitches, or other regulatory elements. We describe a strategy that exploits the entirety of available bacterial genomes to classify all noncoding elements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 39 publications
(45 reference statements)
1
77
0
Order By: Relevance
“…This arrangement suggests that the remaining part of the longer conserved region could be involved in interactions with potential RsaOG targets because such non-structured conserved elements in sRNAs are often involved in trans-pairing. 3 Taken together, these results suggest that the pseudoknot could, by constraining the structure, protect this conserved unpaired region and nucleate or facilitate pairing to the target.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…This arrangement suggests that the remaining part of the longer conserved region could be involved in interactions with potential RsaOG targets because such non-structured conserved elements in sRNAs are often involved in trans-pairing. 3 Taken together, these results suggest that the pseudoknot could, by constraining the structure, protect this conserved unpaired region and nucleate or facilitate pairing to the target.…”
Section: Resultsmentioning
confidence: 84%
“…3 A northern blot experiment indicated that the rsaOG gene was highly expressed. RsaOG was detected at all growth stages but with a progressive increase in post-exponential and stationary phase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations